Privacy's Problem and the Law of Criminal Procedure - Stuntz, William J. (1995)
Part I of this article addresses the connection between privacy-based limits on police authority and substantive limits on government power as a general matter. Part II briefly addresses the effects of that connection on Fourth and Fifth Amendment law, both past and present. Part ID suggests that privacy protection has a deeper problem: it tends to obscure more serious harms that attend police misconduct, harms that flow not from information disclosure but from the police use of force. The upshot is that criminal procedure would be better off with less attention to privacy, at least as privacy is defined in the doctrine today. Were the law of criminal procedure to focus more on force and coercion and less on information gathering (a change that is already beginning to happen), it would square better with other constitutional law and better protect the interests most people value most highly